PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, KOMPENSASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN (Value : Jurnal Manajemen dan Akuntansi, 2022)
Human resources are crucial to attaining corporate objectives. Businesses will be able to compete effectively and continue to advance in a better path if they are backed by people who perform at high levels in all aspects of their jobs. This study intends to ascertain the partial and concurrent effects of democratic leadership style, remuneration, and communication on employee performance. This study's methodology makes use of quantitative research techniques. 33 persons made up the study's sample. The data analysis technique uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F Test and t Test. According to the study's findings, democratic leadership style, compensation, and communication all had a significant impact on employee performance. Democratic leadership style also had a significant impact on compensation, and communication had a significant impact on democratic leadership style and employee performance. Suggestions that can be given by researchers are leaders of UD. Merta Nadi PS in Tabanan is expected to always apply a democratic leadership style in leading his subordinates, in addition, leaders should make compensation policies that are fair and in accordance with the workload of employees and foster communication between employees.Keywords: Leadership, Compensation, Communication, Employee Performance AbstrakSDM pada organisasi memiliki peran penting agar menggapai tujuan industri. Tingkat hasil kerja karyawan yang tinggi akan menunjang perusahaan mampu bersaing secara kompetitif dan berkembang lebih baik. Tujuan riset berikut yakni memahami pengaruhnya gaya kepemimpinan demokratis, kompensasi serta komunikasi dengan cara berparsial serta bersimultan kepada kinerja pegawai. Metode dalam penelitian adalah kuantitatif dengan sampel jenuh atau sensus sejumlah 33 individu. Teknik menganalisis data pada riset mempergunakan pengujian reabilitas, pengujian validitas, menganalisis regresi liner berganda, pengujian asumsi klasik, pengujian T, pengujian F, serta pengujian koefisien determinasi. Hasil dari penelitian adalah bahwa gaya kepemimpinan demokratis ada pengaruhnya positif bersignifikan kepada hasil kerja pegawai, kompensasi ada pengaruhnya positif bersignifikan kepada hasil kerja pegawai, komunikasi ada pengaruhnya positif bersignifikan kepada hasil kerja pegawai, sementara gaya kepemimpinan demokratis, kompensasi dan komunikasi ada pengaruhnya bersignifikan kepada kinerja karyawan. Saran di riset ini yakni pemimpin UD. Merta Nadi PS di Tabanan diharapkan selalu menerapkan gaya kepemimpinan demokratis dalam memimpin bawahannya, selain itu pemimpin hendaknya membuat kebijakan kompensasi secara adil serta sejalan terhadap beban kerja pegawai serta membina komunikasi yang terjalin antar pegawai.Kata kunci :   Kepemimpinan, Kompensasi, Komunikasi,  Kinerja Karyawan